ANALISIS PELAKSANAAN KURIKULUM 2013 DALAM PEMBELAJARAN DI KELAS I SDN 05 KECAPI JEPARA (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This study aims to discuss whether or not there are changes in the implementation of Curriculum 2013 and how to apply Curriculum 2013 in Class I learning at SDN 05 Kecapi Jepara. This research is a descriptive qualitative research with the research subjects of students and full professors of class I SDN 05 Kecapi. Research data obtained through interviews, observations and documentation. The data that has been collected will then be analyzed through data reduction, data presentation and conclusions. The results showed that the implementation of the 2013 curriculum in the I SDN 05 Kecapi class changed slightly, where learning was not carried out in an integrated thematic way, but separately between lessons and the use of the learning were also separated. However, the essence of K13 is still felt in the implementation of learning, where teaching materials always refer to K13. A student-centered scientific approach is also applied to classroom learning I at SDN 05 Kecapi, so that students remain active while learning. Student activity is highly visible when the teacher implements the learning model using digital cards, where students enthusiastically answer questions and practice in front of the class. The teacher also shows an assessment that includes cognitive (test), affective (observation) and psychomotor (practice) aspects.